RED BLOOD CELL INDICES IN PATIENTS WITH CARDIOVASCULAR DISEASES AT A TERTIARY CARE HOSPITAL PESHAWAR - KHAN , A; GOHAR , F; AHMAD , J; HUMAYUN , L; KHAN , A; REHMAN , AK (Biological and Clinical Sciences Research Journal, 2024)
Cardiovascular diseases are a major cause of health loss worldwide, regardless of a country’s income, social status, or demographics. Many studies have reported a link between haematological parameters and cardiovascular diseases in patients. This study aimed to determine the red blood cell indices in patients with cardiovascular diseases at a tertiary care hospital in Peshawar. The study was conducted for six months, from January 1, 2023, to June 30, 2023, at the Pathology Department of Afridi Medical Complex and Teaching Hospital. Blood samples were taken from patients in EDTA vacutainers, and their haematological parameters were determined in the laboratory. The patients’ clinical examinations, history, name, gender, age, and previous laboratory investigations were recorded in a proforma designed for this research. The data were analyzed using IBM SPSS version 23. The study enrolled 80 patients with cardiovascular diseases, including 44 (55%) male and 36 (45%) female patients. The mean age of the study participants was 47 years, with a standard deviation of ±12.3. The mean (±SD) haemoglobin, red blood cell count, hematocrit, mean corpuscular haemoglobin, red cell distribution width-SD, and red cell distribution width-CV were 13.99 (±1.86) (g/dl), 4.49 (±0.55) (million/cm3), 40.72 (±5.81), 28.99 (±2.22), 62.06 (±6.99), and 16.87 (±3.39), respectively. The study concludes that red blood cell indices such as red cell distribution width, haemoglobin, and mean corpuscular volume play a significant role in the pathogenesis of cardiovascular diseases. Routine health examinations and proactive precautions may help lower cardiovascular disease incidence.